The post-operation exercise for patients suffering from inner ear disorder - Zahra Pishnemazi (Iran University of Medical Sciences, 1993)
Surgery to remove some part of the inner ear is an effective intervention to relieve of symptoms. An informed care can decline the patient's fears, and also a pre-operating patient education can facilitate the patient's recovery. Patients, who are in a labyrinthectomy waiting list, feel a combination of anxiety and release. They have spent lots of time to find a treatment for their severe ear disorder. The symptoms of this disease include hearing loss, tinnitus, and acute vertigo accompanied by nausea and vomiting, and also nystagmus (uncontrolled eye movements). Since the labyrinth is impaired unilateral, these patients during walking tend to bend toward the affected side